Z Generation: Living in Society 5.0 Or Learning Religious Science in Pesantren - Dwiaryanti, Risca (Abjadia : International Journal of Education, 2023)
In the contemporary landscape, the age-based classification of individuals has gained prominence, with a focus on Generation Z, encompassing those aged between 11 and 28 years. This Generation, shaped by rapid technological advancements, particularly embraces social media as a pivotal digital platform. This research aims to investigate whether Generation Z prioritizes Society 5.0 ideals or emphasizes religious knowledge within the constraints of pesantren, where social media use is restricted. Employing a quantitative survey design with purposive sampling, the study included 100 respondents, conducting a comparative analysis between public school and pesantren students. The findings, presented through tables and graphs, underscore Generation Z's open-mindedness and their inclination towards socializing through social media to connect with their community. Public school students perceive social media as beneficial, acknowledging its negative impacts. Conversely, pesantren students prioritize religious education for their future. Despite limited social media access, they express a desire to utilize it to stay informed about technological developments in Society 5.0. The results indicate that 80% of Generation considers social media indispensable, irrespective of their educational setting. This study provides valuable insights for students, parents, and educational practitioners, highlighting the intricate relationship between Generation Z, social media, and its multifaceted impacts on their future. It suggests the need for a balanced approach in addressing the diverse needs and preferences of this Generation in different educational environments.